A new understanding of the cognitive reappraisal technique: an extension based on the schema theory - Wang, Ya-Xin; Yin, Bin (Frontiers in Behavioral Neuroscience, 2023)
Cognitive reappraisal is a widely utilized emotion regulation strategy that involves altering the personal meaning of an emotional event to enhance attention to emotional responses. Despite its common use, individual differences in cognitive reappraisal techniques and the spontaneous recovery, renewal, and reinstatement of negative responses across varying contexts may limit its effectiveness. Furthermore, detached reappraisal could cause distress for clients. According to Gross’s theory, cognitive reappraisal is an effortless process that can occur spontaneously. When guided language triggers cognitive reappraisal as an emotion regulation strategy in laboratory or counseling settings, clients experience improved emotional states, but this induced strategy may not necessarily guide them in regulating emotions in similar future situations. Therefore, effectively applying cognitive reappraisal techniques in clinical practice to help clients alleviate emotional distress in daily life remains a significant concern. Exploring the mechanism of cognitive reappraisal reveals that reconstructing stimulus meaning is akin to extinction learning, which entails fostering cognitive contingency that the original stimulus provoking negative emotions will no longer result in negative outcomes in the current context. However, extinction learning is a new learning process rather than an elimination process. The activation of new learning relies on the presentation of critical cues, with contextual cues often playing a vital role, such as a safe laboratory or consulting room environment. We propose a new understanding of cognitive reappraisal based on the schema theory and the dual-system theory, emphasizing the significance of environmental interaction and feedback in constructing new experiences and updating schemata. This approach ultimately enriches the schema during training and integrates the new schema into long-term memory. Bottom-up behavioral experiences as schema enrichment training provide the foundation for top-down regulation to function. This method can assist clients in activating more suitable schemata probabilistically when encountering stimuli in real life, forming stable emotions, and achieving transfer and application across diverse contexts.